(untitled) (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2024)
MSMEs are the most common economic activity carried out by the Indonesian people to generate income for survival. The role of MSMEs in the Indonesian economy is not only as a labor absorber, but also as a place to introduce local products to the international market. Mattiro Ade Village, Patampanua District, is an area in Pinrang Regency with the majority of the population working as farmers. One of the commodity products that are widely cultivated is rice. Therefore, this program focuses on the Service Activities of processing rice into jeepang, with the aim of building a creative and productive MSME sector and creating jobs. This Research and Service activity aims to understand and analyze the development of MSME entrepreneurship through a case study of making jipang in Mattiro Ade Village, Patampanua District, Pinrang Regency. The research method used was a survey with descriptive data analysis. The results showed that MSMEs making jipang cakes (Pilarbark D’legn) can be a new business opportunity that can be run by the local community. It is hoped that this will encourage community productivity, creativity and innovation in creating new things.